Pengolahan Sirup Buah Pedada (Sonneratia caseolaris) dan Keripik Daun Jeruju (Acanthus ilicifolius) di Desa Teluk Pambang Kecamatan Bantan Kabupaten Bengkalis - Trisla Warningsih; Kusai Kusai; Andarini Diharmi; Tomi Ramadona; Chicka Willy Yanti; Deviasari Deviasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Community service activities are making processed products as various food products based on the potential of local plants by utilizing the fruit and leaves of mangroves (Sonneratia caseolaris) and (Acanthus ilicifolius) in Teluk Pambang Village. This activity has the aim of developing the business of processing pedada fruit syrup and jeruju leaf chips using mangrove raw materials from local potential with the objectives of: a) technological innovation of processing mangrove leaves and fruit as product raw materials; b) utilization of processed mangroves for food products that have economic value; c) manufacture of processed mangrove products as an altervative to increase people’s income; d) products packaging; and e) increasing the capacity of business management and marketing of processed products from mangroves. The method used is counseling and practice of processing pedada fruit syrup and jeruju leaf chips. The target community in this activity is the mother of the KPM BELUKAP group in Teluk Pambang Village. The results of the activity show that the community strongly agrees with this activity, being involved in practicing the processing of pedada fruit syrup and jeruju leaf chips as an alternative to increase income. Economic analysis of processed pedada fruit syrup is IDR252,000.00,- and jeruju leaf chips are IDR622,400.00,-. After is this service activity shows that there is a culinary business opportunity that is made from mangroves and can be used by the Teluk Pambang Village community to develop mangroves which were originally only for the tourism sector, as well as to cultivate and preserve mangroves.